(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2024)
The study’s objectives included assessing the levels of endothelin-1 and angiogenin in hypertensive individuals as well as certain biochemical markers. Ninety blood samples were used in this investigation; sixty samples were from hypertension patients and thirty samples were from healthy individuals. The patient’s age ranged from 25 to 70 years old, and both sexes received the same diagnosis from a specialist physician. Between January 10, 2023, and December 20, 2023, samples were taken from hypertension patients at the cardiovascular centers of Al-Dhuluiya and Balid General Hospital in Salah Al-Din. The level of endothelin-1 and angiogenin was assessed, along with a few physiological indicators such as blood electrolytes (potassium and sodium ions), aspartate aminotransferase activity, and body mass index computation. According to the findings, potassium and angiogenin were significantly low in the hypertensive patients spacimens compared with normotensive persons. But the level of Endothelin-1, Sodium, Aspartate aminotransferase activity, and calculation of Body Mass Index show significant elevated in the hypertensive patients compared with normotensive persons. So this study can conducte that the angiogenin, endothelin-1, Na, K, and body mass index may effect on the hypertension and increase the blood pressure, but Aspartate aminotransferase activity is affect by hypertension.